The Influence of Sharia Commitment on Business Sustainability Among Interest-Free Communities in the Soloraya Region - Subando, Joko; Syamsuddin, Syamsuddin; Nisa, Izzun Khoirun; Al Indisi, Muhammad Yahya Ayas; Hendoyo, Muhammad Fajar; Haqa, Muhammad Nazihul (Iqtishodia: Jurnal Ekonomi Syariah, 2025)
This study aims to examine the influence of commitment to Sharia commands and prohibitions on financial growth and business sustainability among interest-free communities. The research focuses on the impact of commitment to Sharia commands and prohibitions on financial growth, strategic sustainability, and the sustainability of business organizational structures. A quantitative method with a survey design was used, involving a sample of 64 respondents in the Soloraya region. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software. The results show that commitment to Sharia commands has a positive and significant effect on financial growth, strategic sustainability, and organizational structure. Commitment to Sharia prohibitions also has a positive and significant effect on financial growth and structural sustainability, but not on strategic sustainability. Simultaneously, both types of Sharia commitment have a significant effect on overall business sustainability from financial, strategic, and structural aspects. These findings highlight the importance of comprehensive implementation of Sharia principles in maintaining sustainable business practices. This research provides a foundation for the development of Sharia business management and supportive policies for interest-free UMKM.